Remembering complexity?: Memorials for Nazi victims in Berlin - Wilke, Christiane (International journal of transitional justice, 2013)
How do memorials shape who we think we are? And how are our identities involved when we debate, create and interact with memorials? This article engages in a conversation with scholarship on intersectional identities and memorial practices in Berlin. Intersectionality scholarship, with its roots in US critical race feminism, has much to offer for thinking about the complexity of identities, yet it does not consider the role of memory, time and temporality. The scholarship on memory and memorials, in turn, does not sufficiently consider the complexity of identities of those who are memorialized and of those who visit memorials. The article asks how two different memorials for Nazi victims in Berlin allow for or facilitate the memory of complex identities, illustrates that memorial practices can be crucial in contemporary identity politics and social movements and calls for a more self-reflexive approach to the role of identities and complexity in memorial scholarship and practice.